Avaliação da biocompatibilidade e potencial angiogênico do látex de Hancornia speciosa - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
Plants are promising sources of new bioactive compounds, especially in the medical field. An important discovery in the area of biomaterials applied to medicine is that the natural rubber from Hevea brasiliensis has potential to regenerate tissues (angiogenesis) and is also biocompatible to living systems. However, some individuals present allergy to natural rubber proteins,which restrain its application. Thus researchers have looking for others lactiferous species with lower allergenic potential. The mangabeira latex could be an alternative, since its amount of protein is lower than natural latex rubber. The latex obtained from Hancornia speciosa, a plant native to Brazil popularly known in Portuguese as “mangabeira”, is used in folk medicine for treatment of several diseases, such as acne, warts, diabetes, gastritis and inflammation. In this work, we describe the biocompatibility assessment and angiogenic properties of H. speciosa latex and its potential application in medicine. The biocompatibility was evaluated through cytotoxicity and genotoxicity in Allium cepa model and the angiogenic properties were evaluated using the chick chorioallantoic membrane (CAM) assay model. As results the cytotoxicity and genotoxicity assays showed that Hancornia speciosa latex is biocompatible with life systems and can be a good biomaterial for medical applications. The CAM test showed the efficient ability of Hancornia speciosa latex in neovascularization of tissues. The histological analysis was in accordance with the results obtained in the CAM assay. Our data indicate that the latex obtained from H. speciosa and eluted in water showed significant angiogenic activity without any cytotoxic or genotoxic effects on life systems. This study contributes to the understanding of the potentialities of Hancornia speciosa latex as a source of new phytomedicines.
Keywords: Angiogênese; Biomaterial; Citotoxicidade; Mangaba; Genotoxicidade; Angiogenesis; Biomaterial; Cytotoxicity; Genotoxicity; CIENCIAS AGRARIAS